Distraction and consumer behavior: Evidence from a natural field experiment - Sven-Olov Daunfeldt; Hampus Poppius; Niklas Rudholm (Institute of Retail Economics (HFI), 2019)
This paper explores how distraction from a consumer's surroundings may influence consumption. In a natural field experiment involving 16 fastfood restaurants over five months, we randomly varied the degree of familiarity of the background music. We find that playing familiar music reduces revenues and quantity sold by more than 4 % relative to playing similar but unfamiliar music. We conduct a complementary survey that suggests that the reason that familiar music reduces consumption is that it distracts consumers. We conclude that when consumers become distracted, they consider fewer consumption opportunities and therefore consume less. The results have implications for the literature on attention and framing as well as for marketing policy.
Keywords: D89; D91; L83; M31; 330; consumer behavior; natural field experiment